SPREAD OF PARASITIC DISEASES AMONG THE POPULATION OF CITY GULISTAN - Islambek A. Kudiyarov; Mehriban O. Zaydullayeva; Gulsara A. Seyfullayeva (Central Asian Journal of Medicine, 2024)
The dynamics of parasitic diseases of the population of the city Gulistan were compared with the results of helminthological examinations of open water bodies, soil, fruits and vegetables, meat, and fish products used by the population for drinking and household purposes. In 2022, a weak correlation was found between the level of parasitic diseases in the city Gulistan and the level of contamination indicators of soil, fruit, and vegetable samples (rxy=0.17; mr=0.01), and no correlation was detected with open water bodies, meat, and fish products.